Dynamic change and driving force of natural capital in Qinghai Province based on the three-dimensional ecological footprint, China - Jing Guo; Zhen Wei; Xianrong Xie; Jun Ren; Huakun Zhou (Ecological Indicators, 2022)
Natural capital is a basic condition for human survival, and its utilization evaluation is the core issue of regional sustainable development. Based upon the improved three-dimensional ecological footprint model, this study discusses the dynamic changes in natural capital time series and spatial patterns in Qinghai Province from 2011 to 2020. The driving factors of ecological footprint change were revealed using partial least squares (PLS). The results demonstrate that (1) from 2011 to 2020, the per capita ecological footprint of Qinghai Province will increase from 2.505 hm2/person to 3.125 hm2/person. The per capita ecological capacity is affected by resource endowment and is maintained at 3.982–4.160hm2/person, thus indicating a weak downward trend year by year. (2) During the study period, the per capita EFdepth, of Qinghai exhibited an overall growth trend and increased from 1.299 hm2/person to 1.419 hm2/person. The per capita EFsize was primarily affected by the ecological capacity and reached the highest value of 1.352hm2/person in 2019. The three-dimensional model demonstrates that the per capita EFsize (bottom area) changes slightly during the four periods. (3) Over the past 10 years, the capital flow occupancy rate of Qinghai Province has increased from 26.23 % to 30.90 % with an average annual growth rate of 1.65 %, this indicating a large potential for natural capital utilization. (4) The PLS model revealed that energy consumption, ecological construction, social consumption, population, and economic development are the primary factors affecting the increase in natural capital utilization in Qinghai Province. This study aims to provide a reference for promoting regional sustainable development goals, for achieving coordinated development of resources, the environment, and the social economy, and for accelerating the construction of ecological civilization.